Positive Feedback Stimulation of Ccnb1 and Mos mRNA Translation by MAPK Cascade During Mouse Oocyte Maturation - Cao, Lan-Rui; Jiang, Jun-Chao; Fan, Heng-Yu (Frontiers in Cell and Developmental Biology, 2020)
In mammalian species, both the maturation promoting factor (MPF, a heterodimer composed of CDK1 and cyclin B1) and the mitogen-activated protein kinase (MAPK) cascade play pivotal roles in regulating oocyte meiotic cell cycle progression. Activation of MPF and ERK1/2 requires translational activation of maternal Ccnb1 and Mos mRNAs, respectively. ERK1/2-triggered phosphorylation and degradation of CPEB1 is a major mechanism of maternal mRNA translational activation. However, the interplay of these two key kinases in mediating translation activation of cytoplasmic mRNAs during mammalian oocyte maturation is unclear. We provide evidence that Ccnb1 transcripts containing a long 3′-UTR undergo translational activation during meiotic resumption in an ERK1/2-dependent manner. A low level of ERK1/2 activation was detected prior to meiotic resumption. Precocious activation of MAPK signaling in germinal vesicle stage oocytes promotes the translation of Ccnb1 mRNA and meiotic maturation. Inhibition or precocious activation of CDK1 activity has an appreciable effect on the translation of Ccnb1 mRNA, suggesting that both kinases are required for Ccnb1 mRNA translational activation. CDK1 triggers phosphorylation, but not degradation, of CPEB1 in oocytes; the degradation of CPEB1 was only triggered by ERK1/2. Moreover, the translational activation of Mos mRNA is also regulated by ERK1/2 and cytoplasmic polyadenylation elements. Taken together, the cooperation and positive feedback activation of ERK1/2 and CDK1 lead to the fine-tuning of mRNA translation and cell cycle progression during mouse oocyte maturation.